Detection of Sutterella spp. in Broiler Liver and Breast - Derqaoui, Sophia; Oukessou, Mohammed; Attrassi, Kawtar; Elftouhy, Fatima Zahra; Nassik, Saadia (Frontiers in Veterinary Science, 2022)
Sutterella spp is a gram-negative, microaerophilic bacterium that is particularly resistant to bile acids. The objective of this study is to identify, for the first time, Sutterella spp. in the liver and breast of broiler chickens by RT-PCR. Liver, breast and cæcal content samples were taken from 25 individuals and frozen at -20°C until analyzed. The main results showed that Sutterella spp. is a part of the cæcal microbiota of 48% of the individuals and present in the liver and breast of respectively 20% and 40% of the individuals with a variable Cq. We, therefore, conclude that Sutterella spp. exists in poultry and poultry meat and foodstuffs of poultry origin might be considered as a potential source of contamination for humans.